Fundamentalist world : the new dark age of dogma - Sim, Stuart, 1943- (Cambridge : Icon, 2004)
The collapse of the Argentinian economy, the rise of the far right, 9/11, suicide bombings in the Middle East, campaigns against multiculturalism, anti-abortion terrorism, the militia movement in America, teaching creationism in schools, riots at Miss World: what ties these seemingly unrelated phenomena together?. All are products of a fundamentalist mentality, determined to crush all opposing ideas. Belief in these kinds of universal theories was, until recently, assumed to be in decline. Stuart Sim argues that this is far from true.
Includes bibliographical reference and index
Keywords: Fundamentalism; World politics -- 1989-.